2020
DOI: 10.1093/jpepsy/jsaa048
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of an Intervention to Reduce Disparities in School HRQOL for Latino Childhood Cancer Survivors

Abstract: Objective Survivors of childhood leukemia, especially those from low socioeconomic status households, often experience persistent neurocognitive and academic impairment. This study adapted an existing parent training intervention to improve outcomes for low-acculturated, Spanish-speaking Latino parents of children with leukemia and pilot tested that intervention for feasibility. Methods Semistructured interviews were conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Ellis et al [ 22 ] implemented a program in which children connected with their peers at school through videoconferencing, while Inhestern et al [ 23 ] described a family rehabilitation program where children were able to interact with other children with cancer while in the hospital. Parents in two studies received self-efficacy training on how to help their child succeed in school and access school and community resources [ 43 , 49 ]. One study detailed a medical follow-up program for the child and family post-cancer treatment to ensure families received the support they needed and included medical, educational, psychosocial, and neurocognitive follow-up [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Ellis et al [ 22 ] implemented a program in which children connected with their peers at school through videoconferencing, while Inhestern et al [ 23 ] described a family rehabilitation program where children were able to interact with other children with cancer while in the hospital. Parents in two studies received self-efficacy training on how to help their child succeed in school and access school and community resources [ 43 , 49 ]. One study detailed a medical follow-up program for the child and family post-cancer treatment to ensure families received the support they needed and included medical, educational, psychosocial, and neurocognitive follow-up [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Six studies described programs designed to increase parent or school faculty knowledge. Programs included SLPs, meeting with a family advocate, and parent self-efficacy training to improve parent knowledge of available school resources, child school needs, and how to help their child in school [ 42 , 41 , 45 , 35 , 43 , 49 ]. In one study describing a SLP, parents also reported increased school faculty knowledge of their child’s academic needs [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A translated version of Bright Ideas, a problem-solving skills training intervention, is available and has demonstrated greater efficacy in improving problem-solving skills among Spanish-speaking mothers of children newly diagnosed with cancer when compared with English-speaking mothers (Sahler et al., 2005). In addition, two culturally and linguistically adapted interventions for Latinx parents of childhood cancer survivors have demonstrated promise in enhancing children’s academic wellbeing (Bava et al., 2017, 2018; Patel et al., 2020). This work highlights the potential to improve the experience and outcomes of Latinx PCC.…”
mentioning
confidence: 99%